Pengaruh Kompensasi, Keterlibatan Kerja, dan Hubungan Antar Karyawan pada Perumda Pasar Joyoboyo Kota Kediri - Anisa Patrisia; Miftahul Munir; Anita Sumelvia D (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aimed to explain and prove the hypothesis regarding the influence of compensation, work engagement, and interpersonal relationships on employee retention at Perumda Pasar Joyoboyo in Kediri City. Employee retention is a crucial issue in human resource management as it relates to organizational sustainability, recruitment cost efficiency, and long-term performance improvement. This study employed a quantitative approach with a non-probability sampling technique, specifically a saturated sampling method. The entire population of 41 employees was sampled. Data were collected using relevant research instruments and then analyzed using SPSS using the t-test (partial), F-test (simultaneous), and coefficient of determination (R²) to determine the contribution of the independent variables to the dependent variable. The results showed that, partially, compensation and interpersonal relationships had no significant effect on employee retention. Meanwhile, interpersonal relationships had a more prominent effect, and when tested simultaneously, all three variables were found to have a significant effect on employee retention. These findings underscore the importance of interpersonal relationships in the workplace in maintaining employee loyalty and engagement at Perumda Pasar Joyoboyo in Kediri City.